2022
DOI: 10.1002/adma.202200041
|View full text |Cite
|
Sign up to set email alerts
|

A Universal Strategy of Intermolecular Exchange to Stabilize α‐FAPbI3 and Manage Crystal Orientation for High‐Performance Humid‐Air‐Processed Perovskite Solar Cells

Abstract: preparing PSCs out of the glovebox to eliminate expensive costs is necessary for further commercialization. [8][9][10][11][12][13] Even the well-studied methylamine lead iodine (MAPbI 3 ) perovskites exhibit uncontrollable crystallization in humid air, resulting in rough and pinhole-containing perovskite films with multiple defects and thus limiting their performance. [14][15][16][17] Formamidine (FA)-based perovskites have a narrower bandgap and superior stability than MAPbI 3 and have been widely applied in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 50 publications
0
48
0
Order By: Relevance
“…Detailed information on synthesis of materials, 1 H NMR, 13 C NMR, and HRMS spectra; density functional theory calculation, mobility and conductivity measurements, cyclic voltammetry measurement detail, calculation of HOMO and LUMO energy levels, the steadystate PL and TRPL measurements, and the electrochemical impedance spectroscopy (PDF)…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information on synthesis of materials, 1 H NMR, 13 C NMR, and HRMS spectra; density functional theory calculation, mobility and conductivity measurements, cyclic voltammetry measurement detail, calculation of HOMO and LUMO energy levels, the steadystate PL and TRPL measurements, and the electrochemical impedance spectroscopy (PDF)…”
Section: Discussionmentioning
confidence: 99%
“…The champion cell delivered a PCE of 23.7% with excellent stability. 162 Meng et al 161 employed a conjugated donor polymer (PTQ10) as an interfacial layer for the perovskite intermediate phase before thermal annealing. The PTQ10 treatment can significantly suppress the volatilization of the surface organic cations during thermal annealing.…”
Section: Top Surfacementioning
confidence: 99%
“…At the same time, the nHA in the film can also reduce the defects and suppress ion migration. The champion cell delivered a PCE of 23.7% with excellent stability 162 . Meng et al 161 employed a conjugated donor polymer (PTQ10) as an interfacial layer for the perovskite intermediate phase before thermal annealing.…”
Section: Interface Engineeringmentioning
confidence: 99%
“…The additives can enhance the stability of precursor solution and reduce the crystal nucleus, getting large-size high-quality perovskite single crystals. Wang et al [14] demonstrated an intermolecular exchange strategy to prepare stable FA-based perovskites under an air environment, by introducing a longchain n-heptylamine (nHA) additive via antisolvent engineering. This strategy prompts the formation of α-FAPbI 3 and optimizes the grain orientation.…”
Section: Polymer Additivesmentioning
confidence: 99%